Weaving a Universal Narrative: A Comparative Screenplay Analysis of Parasite and Blue Velvet - Goosen, Matthew (Centre for Film and Media Studies, 2024)
Based on a comparative analysis between Blue Velvet (Lynch, 1986) and Parasite, (Joon- Ho, 2019), the purpose of this dissertation is to facilitate the: definitions, possibilities for further research, and a skillset upon which audiences and vocational practitioners might interpret cinematic storytelling, thus allowing scholars, critics, and audiences develop statements on the film's central theme. The approach of this thesis is to appreciate, acknowledge, elaborate upon, and challenge the filmmakers' artistic statements while contributing to the methodologies by which viewers might further appreciate the universality of the cinematic language (Lingua Cinéma). My methodology for this thesis will be to identify and offer a comparative analysis of narrative, visual, and sound elements based on interpretive and evaluative claims to determine and establish a universal film narrative. Blue Velvet (Lynch, 1986) and Parasite (Joon-ho, 2019), despite their cultural and temporal dissimilarities, are both films that are deeply invested in mood, tonality, and symbolism, and deal with post-modern themes such as late-state capitalism by conflating the iconography of the ideal national standard and juxtaposing it with inequity and moral decay. The diversity and similarity of this selection of films, therefore, has served to demonstrate the correlation between cinema and culture, thereby inferring the universality of images, textual analysis, and Lingua Cinéma. Based on the framework consisting of plot and character development; similarities in tone, length, and genre; and the incidence of beat placement, contemporary and subsequent research into the comparative analysis of these two films indicates a correlation between audience and scholarly response and the application of a universal narrative. Interpreting the framework of the cinematic storytelling methodology offers and facilitates formal organization; expectations; aspects of character, story, and structure; interpretation of motifs and parallels; and references to history, tradition, culture, and themes. Offering a universal framework bestows scholars the means by which to develop interpretative and evaluative claims based on organization and a keen insight.